Online taxi users' optimistic bias: China youths' digital travel and information privacy protection - Meng, Xiaoyang; Feng, Bobo (Frontiers in Psychology, 2022)
Digital travel platforms not only provided people with convenient travel but also raised a series of problems regarding information privacy protection. In order to analyze privacy protection behavior, this study surveyed 441 subjects aged 18–35 who utilized digital travel platforms based on a structural model of protective motivation theory. The results indicated that a perceived threat, self-efficacy, and response efficacy positively and significantly impacted youths' privacy concerns. Furthermore, privacy concerns were positively related to privacy protection behavior and were an intermediate variable between the relationships among perceived threat, self-efficacy, response efficacy, and privacy protection behavior. This study identified the moderating effect of youths' knowledge of platform privacy settings on the relationship between privacy concerns and protection behavior. In addition, the results confirmed that an optimistic bias did exist among talented youth with high privacy knowledge in terms of a practical level of privacy management. These unique findings represent the exceptional contributions and innovation points of this study.